A case of a pulmonary artery sling misdiagnosed as refractory asthma for 20 years. Issue 6 (19th April 2017) - Inui, Toshihide; Yamada, Hideyasu; Hida, Norihito; Terashima, Hideo; Saito, Takefumi; Hizawa, Nobuyuki
Key Clinical Message: We report the case of a 25‐year‐old woman with a pulmonary artery sling who was misdiagnosed as having childhood‐onset refractory asthma for approximately 20 years. The use of computed tomography may be useful for diagnosing this rare condition. Abstract : We report the case of a 25‐year‐old woman with a pulmonary artery sling who was misdiagnosed as having childhood‐onset refractory asthma for approximately 20 years. The use of computed tomography may be useful for diagnosing this rare condition.